Students’ Engagement in School: A literature review - Veiga, Feliciano Henriques (2013)
This work is financed by National Founds through FCT-Fundação para a Ciência e Tecnologia, in the context of the project PTDC/CPE-CED/114362/2009- Students Engagement in Schools: Differentiation and Promotion, coordinated by Prof. Feliciano H. Veiga.